PEMBUBARAN KOPERASI YANG TIDAK MENJALANKAN RAPAT ANGGOTA TAHUNAN OLEH DINAS KOPERASI DAN USAHA MIKRO KECIL MENEGAH DI KOTA PEKANBARU - Gultom, Asrini Juniati; Hanifah, Mardalena; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Cooperatives in Indonesia does not have the ability to play its role effectively and strongly Pekanbaru is a city that has a high rate of economic growth, Pekanbaru Proven Having researched many cooperatives that are not well developed or not active, from data obtained from the Department of Cooperatives and SMEs in the city of Pekanbaru number of cooperatives in Pekanbaru In Year 2013 there were 906 cooperative units, a total of 342 units that perform cooperative Annual Meeting of Members, while other cooperative unit 564 is currently inactive status, 213 are inactive but still found and 351 inactive cooperatives were not found.The purpose of this thesis, Basic Considerations First Department of Cooperatives and Small Medium Micro Enterprise Against Dissolution of Cooperative Its not implement the Annual Members meeting in Pekanbaru city, Secondly, the cooperative constraints in implementing the Annual Members Meeting, a result that is not co-operative Law Against Implement Annual Member Meeting in the city of PekanbaruThis type of research is classified into types of sociological research, research on the effectiveness of the law in force, the nature of this research is descriptive research that describe systematically the facts and characteristics of the object under study appropriately. This research was conducted at the Department of Cooperatives and SMEs located Pekanbaru City Lotus Path Number. 84 city of Pekanbaru. Population and the sample is related to the problems examined in this study, which used data sources, primary data and secondary data consisting of primary legal materials, secondary and tertiary, data collection techniques in this study with questionnaires, interviews and studies literature and analysis of data used is the qualitative analysis is based on the description of a sentence and draw conclusions deductively, from the general to the specific. First, Basic Considerations Against Department of Cooperatives and SMEs do not implement the dissolution of the Cooperative The Annual Members meeting in Pekanbaru City is referring to the Article 46 of Law No. 25 of 1992 on Cooperative. Advice Author, First, arrangements should be in his RAT Regarding reiterate Second, Should sanctions and stressed, in order to provide a deterrent effect for each cooperative naughty.